A cell culture system developed from heart tissue of the greasy grouper, - Sobhana, K S; George, K C; Venkat Ravi, G; Ittoop, Gijo; Paulraj, R (Indian Journal of Fisheries, 2011)
Heart tissue samples aseptically excised from healthy juveniles of the grouper, Epinephelus tauvina were subjected to enzymatic dissociation using 0.25 % trypsin solution, under aseptic conditions. The resultant cells were suspended in Leibovitz’ L-15 medium supplemented with 20 % fetal bovine serum. The cells were subsequently seeded into 25 cm 2 tissue culture flasks at a density of 10 6 ml-1 and incubated at 28 Â± 2Â°C. Cells showed spreading and attachment to the culture flasks within 24 h and formed monolayers comprising of epithelioid as well as fibroblast-like cells within 20 days. A confluent monolayer filling the flask surface comprising predominantly fibroblastic cells was formed within 30 to 35 days. The cell monolayer was harvested for passage by trypsinisation, which formed successful monolayers in subsequent subcultures. Â